2022
DOI: 10.1371/journal.pntd.0010235
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with in-hospital mortality of adult tetanus patients–a multicenter study from Bangladesh

Abstract: Background Tetanus, a vaccine-preventable disease, is still occurring in the elderly population of low- and middle-income countries with a high case-fatality rate. The objective of the study was to elucidate the factors associated with in-hospital mortality of tetanus in Bangladesh. Methods This prospective observational study, conducted in two specialized infectious disease hospitals, conveniently selected adult tetanus patients (≥18 years) for inclusion. Data were collected through a preformed structured q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
2
7
1
Order By: Relevance
“…Our study revealed a high proportion of tetanus deaths occurring among those aged 31–40 years. This is in contrast to what Khan et al [ 35 ] reported from Bangladesh, where deaths mostly occurred among older individuals above 60 years of age. We recommend further studies to assess risk factors for mortality in our setting.…”
Section: Discussioncontrasting
confidence: 93%
“…Our study revealed a high proportion of tetanus deaths occurring among those aged 31–40 years. This is in contrast to what Khan et al [ 35 ] reported from Bangladesh, where deaths mostly occurred among older individuals above 60 years of age. We recommend further studies to assess risk factors for mortality in our setting.…”
Section: Discussioncontrasting
confidence: 93%
“…Although such affections might be the primary cause of trismus, they could disguise superposed tetanus in some cases, especially in underlying compound mandibular fractures or facial lacerations [6,30,38]. In our study, the interval between trismus and death was relatively short (4.25±1.89 days), which is concordant with other studies [22,39]. Trismus is tetanus's most common premonitory symptom, followed by dysphagia and cervical stiffness [6,9,40].…”
Section: Discussionsupporting
confidence: 91%
“…Given the high lethality, the relevance of early diagnosis is obvious. A delay in treatment can be fatal [20,22,[31][32][33][34][35]. According to our results, the lethality of odontogenic tetanus was 30.77%.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations